Caracterização fisiológica da deficiência de magnésio em mudas de Coffea arabica L. submetidas ao calor - Silva, Dayane Meireles da (2017)
Aimed with this study investigate the importance of adequate magnesium nutrition in Coffea arabica L. seedlings cv. Catuaí submitted to heat stress. In this way, seedlings were transferred to plastic recipient contain a nutrient solution with different magnesium concentrations and subjected to two temperatures (25 and 35 °C). Fully expanded leaves and roots were collected at the beginning of the experimental period and after 10, 20 and 30 days. Variable analyzed were dry weight production, magnesium, total chlorophyll, total soluble sugar, reducing sugar, sucrose, starch, hydrogen peroxide, proline, ascorbate, malondialdehyde, protein and amino acid, invertases activity, dismutase of superoxide, catalase, ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase and glutathione reductase. These analyzed variables were affected mainly by the combination of stress, Mg-deficiency and heat stress. Alone or in combination these stresses increase shoot:root dry weight ratio, which may be related to carbohydrates accumulation in leaves and its reduction in roots. Invertases activity was negatively affected by both stresses, being the combination of these stresses responsible for the lowest activities. With this decrease in invertase activity, roots showed a reduced activity and consequently its strength in attracting photoassimilates stayed compromised. In addition, Mg deficiency and heat stress caused an increase in hydrogen peroxide concentration, which was accompanied by a higher activity of antioxidant metabolism and higher production of proline and ascorbate. However, the antioxidant metabolism was inefficient in reactive oxygen species removal, resulting in high lipid peroxidation and protein degradation. When submitted to heat, coffee seedlings with Mg showed lower physiological damages than those Mg-deficient. Therefore, greater attention is required about magnesium nutrition in Coffea arabica L. seedlings cv. Catuaí in order to mitigate the losses due to heat stress.